2017
DOI: 10.1111/jce.13290
|View full text |Cite
|
Sign up to set email alerts
|

Chronic total occlusion in an infarct‐related coronary artery and the risk of appropriate ICD therapies

Abstract: IRA-CTO is an independent predictor of appropriate ICD therapies, including appropriate ICD shocks. This association is consistent across all the subgroups analyzed. Patients with IRA-CTO have a very high risk of appropriate ICD therapies. These findings may help improving risk stratification as well as the management of ventricular arrhythmias in patients with ischemic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 30 publications
4
26
1
1
Order By: Relevance
“…Di Marco et al have shown that the presence of a CTO in a previous infarcted area (infarct‐related artery [IRA]‐CTO) is associated with the occurrence of more VA (especially fast VT/VF) and more ICD therapy 18, 19. VT ablation could be an appropriate treatment option in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Marco et al have shown that the presence of a CTO in a previous infarcted area (infarct‐related artery [IRA]‐CTO) is associated with the occurrence of more VA (especially fast VT/VF) and more ICD therapy 18, 19. VT ablation could be an appropriate treatment option in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Di Marco et al have shown that the presence of a CTO in a previous infarcted area (infarct-related artery [IRA]-CTO) is associated with the occurrence of more VA (especially fast VT/VF) and more ICD therapy. 18,19 VT ablation could be an appropriate treatment option in these patients. Nevertheless, Di Marco et al have also shown that the presence of an infarct-related artery-CTO is an independent predictor of VT recurrence after VT ablation, compared with patients with prior myocardial infarction without an infarct-related artery-CTO.…”
Section: Currently Available Datamentioning
confidence: 99%
“…Several reports suggest that patients with CTO, and especially with IRA‐CTO, are at high risk for ventricular arrhythmias. Moreover, patients with IRA‐CTO have more arrhythmogenic substrate (greater scars with greater border zone) .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic total occlusions (CTOs), especially when located in an infarct‐related coronary artery (IRA‐CTO), are emerging as independent predictors of appropriate implantable cardioverter defibrillator (ICD) therapies both in primary and secondary prevention ICDs . Moreover, IRA‐CTO is a strong and independent predictor of VT recurrence after ablation .…”
Section: Introductionmentioning
confidence: 99%
“…Тем не менее, наличие хронической окклюзии определенным образом ассоциировано с электрической нестабильностью миокарда и угрозой развития жизнеугрожающих аритмий. Пациенты с ХОКА, у которых были имплантированы кардио вертеры-дефибрилляторы для первичной и вторичной профилактики внезапной сердечной смерти, имели более высокую частоту срабатывания прибора по сравнению с группой пациентов без ХОКА [12]. ХОКА в зоне инфаркт-связанной КА выступает как независимый предиктор 2-3 кратного увеличения количества желудочковых аритмий даже после аблации желудочковых аритмий [12,13].…”
Section: Introductionunclassified